رسالة الحاسد والمحسود للجاحظ: دراسة في الدلالة والتشكيل - سلامي، سميرة (جامعة دمشق, 2016)
أوضح البحث عناية الجاحظ بأدب الطباع، وفلسفة الأخلاق، من خلال تناوله لطباع فئة من البشر، هي فئة الحساد، كما حدد مفهوم الحسد عند الجاحظ، وماهيته، وأسبابه وعلله. وبين صفات الحاسد، وأخلاقه، وعلاماته، وكيف يعرف ظاهره وباطنه، ولماذا كثر بين الأقرباء والجيران، وصار في العلماء أكثر منه في الجهلاء. وتناول البحث، أيضا، المحسود، فبين أنه من ذوي النعم، على تنوعها واختلافها، وأن شر الحاسد يلاحقه على الدوام، وشر الحاسد لا يقتصر على المحسود، بل يمتد ليطال المجتمع بأسره، ولا ينجو منه الحاسد نفسه. ولم يجد الجاحظ علاجا للحاسد، إلا بمقاطعته وعدم مخالطته. وبين البحث، أن الجاحظ جمع كل ما وعاه عقله، مما قاله القدماء عن الحسد والحاسد والمحسود، واختار منه ما يتناسب ونزعته الفنية، التي طغت على الرسالة، مضيفا إلى ذلك تجربته المضنية مع الحساد، الذين طعنوا في كل ما كتب. ووجد البحث في الرسالة، أنموذجا لمنهج الجاحظ في الكتابة، ولطريقته وأسلوبه، ولسمات مدرسته الفنية. وقد صاغها بقلمه الساحر، وبيانه الأخاذ، فجاءت قطعة فنية خالدة.
This research paper studies the Hasid and Mahsoud by Al-Jahiz from two basic perspectives: First: From a semantic viewpoint that portrays the feeling of envy harbored in the inner life of a person, and is self destructive hitting on one's own spirit. The feeling of envy as a concept captured by Al-Jahiz is thoroughly described, its causes enumerated, its effects explained, as well as the know how to discern its essence from the ways it is vented out through the acts, character, and behavior of a person. Al-Jahcz continues to discuss how and why such a social phenomenon, a mentality became so wide spread beleaguering relatives, neighbors, and even scholars more often than laymen. He elaborated on who is the subject of envy, and causes behind such ill feelings. He moves on to thoroughly depict the person who harbors a general sense of envy, his characteristics, inner pain, malice, and how to break away from such negative sentiments fending off its effects. Secondly: The research paper approaches this work of Al-Jahiz from aesthetic viewpoint highlighting the distinctive features of his style. A number of key issues are brought under the limelight: the controversial debate of quoting anon),. rnous, sometimes well known figures, the rhetorical devices and aesthetics of his language. This masterpiece is a sample of Al-Jahiz literary talent, philosophical approaches, style, and distinctive touches of what later became a literary trend called after him displaying his craftsmanship, and captivating language.
Keywords: الأدب العربي -- رسالة الحاسد والمحسود -- الجاحظ، عمرو بن بحر بن محبوب، ت. 255 هـ. -- الحسد -- النقد الأدبي